Little wars: the geopolitics of 20th century board games - Harby, Alexander (2019)
Political and cultural geographers are increasingly engaging with the political aspects of play. This "ludic geopolitics" is often studied through video games, particularly war games which place the player in virtual battlefields and reproduce geopolitical discourses. But this work is ahistorical; it has overlooked the contributions that board games over the 20th century have made to shaping and reproducing popular geopolitics. In this thesis, I reveal these contributions by analysing twenty British war games produced in the early 20th century, from the Second Boer War to the Second World War. I discuss their visual contents and forms, the ways in which their rules function, and their historical contexts to show how they circulate popular geopolitics and discourses of militarism in response to Britain's ever-changing geopolitical climate. Recurring tropes engage in these board games that historicise modern ludic geopolitical work on video games. These games engage with British popular geopolitics in various ways, by reproducing wartime propaganda, simulating past conflicts, or even making their geopolitical contexts deliberately absent in the game's contents. But even when war games are ambivalent, they circulate similar popular discourses of militarism, demonstrating technofetishism and representing wars as bloodless and as inherently masculine.